The appraisal of the scope for the application of nuclear magnetic resonance (NMR) measurement methods for the estimation of the biological age in various stages of human ontogeny - Czapla, Zbigniew; Fojud, Zbigniew (Adam Mickiewicz University, Faculty of Biology, 1999)
The main objective of the study is to find a new physical parameter meeting the criterion of the biological age estimation in various stages of human ontogeny, and thus to find a new research methodology for this field of research. For this purpose an NMR Bruker 200 MHz spectrometer was used. Two physical parameters: relaxation time (T1) and spectrum shape were determined. The research material was oral mucosa epithelium sampled in a group of young people of both sexes (31 subjects) and in a group of men (18 subjects). Relaxation time (T1) and spectrum shape were recorded for hydrogen nuclei (H1). The physical phenomena were analysed statistically (regression analysis) and their biological interpretation was attempted.
Keywords: Electrophoretical Mobility of Cell Nuclei; human ontogeny; aging; biological age; free radical theory of aging; Nuclear Magnetic Resonance; spin-lattice relaxation time; chemical shift